GENÇ ERKEK HASTADA DEV ÜRETER TAŞI: OLGU SUNUMU - ÖZKAN, Burak; SANCAKLI, Özgür; DEMİRKESEN, Oktay (Cerrahpaşa Medical Journal, 2014)
Backgroud and Design.- Ureteral stones are usually small and arise from the kidney. The term giant has been applied to ureteral stones that are more than 5 cm length and/or 50 gr. or more in weight. Here in we report a case of a giant ureteral stone in a 37 year old man, presented with right flank pain referred to our clinic. Radiological examinations revealed right hydronephrosis with a giant ureteral stone. Open ureterolitotomy was performed and the stone was removed. The ureteral stone was measured as 6 cm long and weighed 59 gr. Patient was discharged from the hospital at 4th day postoperatively without any complication. Giant ureteral stones are uncommon. They may be asymptomatic and therefore might be missed. The damage in the renal unit changes with respect to the degree of the obstructive uropathy. Treatment options for large ureteral stones are open and laparoscopic ureterolithotomy.